A Lung Ultrasound Severity Score Predicts Chronic Lung Disease in Preterm Infants - Abdelmawla, Mohamed; Louis, Deepak; Narvey, Michael; Elsayed, Yasser (American Journal of Perinatology, 2019)
Objective To test the hypothesis that a lung ultrasound severity score (LUSsc) can predict the development of chronic lung disease (CLD) in preterm neonates.Study Design Preterm infants <30 weeks' gestational age were enrolled in this study. Lung ultrasound (LUS) was performed between 1 and 9 postnatal weeks. All ultrasound studies were done assessing three lung zones on each lung. Each zone was given a score between 0 and 3. A receiver operating characteristic curve was constructed to assess the ability of LUSsc to predict CLD.Results We studied 27 infants at a median (interquartile range [IQR]) gestational age and birth weight of 26 weeks (25–29) and 780 g (530–1,045), respectively. Median (IQR) postnatal age at the time of LUS studies was 5 (2–8) weeks. Fourteen infants who developed CLD underwent 34 studies. Thirteen infants without CLD underwent 30 studies. Those who developed CLD had a higher LUSsc than those who did not (median [IQR] of scores: 9 [6–12] vs. 3 [1–4], p < 0.0001). An LUSsc cutoff of 6 has a sensitivity and specificity of 76 and 97% and positive and negative predictive values of 95 and 82%, respectively. Adding gestational age < 27 weeks improved sensitivity and specificity to 86 and 98% and positive and negative predictive values to 97 and 88%.Conclusion LUSsc between 2 and 8 weeks can predict development of CLD in preterm neonates.
Keywords: lung ultrasound; preterm infants; chronic lung disease